Pelatihan Pertolongan Pertama Sebagai Ketrampilan Penanganan Kedaruratan Medis Pada Santri Madrasah Aliyah - Wijaya, Liza (LPPM STIKES Madani, 2022)
Accident is an emergency that can affect shock, physical damage, and even death. The highest prevalence of injury occurred in the 15-24 year age group. School-age is very vulnerable to accidents in the school environment. Some cases of injuries occurred in school include fainting, traffic injuries, falls, insect stings, and poisoning. Red Cross Youth (ind-PMR) activity is an extracurricular activity in the health sector that is prepared to assist medical emergencies that occur in the school environment. Good knowledge and appropriate skills are needed in providing first aid to reduce the degree of pain and prevent the condition from getting worse. This community service was carried out 3-31 March 2022 to facilitate skills in handling medical emergency cases in the Madrasah Aliyah Islamic Centre Bin Baz Islamic Boarding School environment. This service was attended by 16 female students who became members of PMR by using the simulation method and evaluation was carried out by observing the actions taken again. Results of the overall evaluation are each student is able to understand and carry out first aid actions well in each case and can be used as a basis for the person in charge of extracurricular activities to integrate first aid materials as part of curriculum learning